2012
DOI: 10.1021/nl300563h
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electronic Transport in Graphene Wrinkles

Abstract: Wrinkling is a ubiquitous phenomenon in two-dimensional membranes. In particular, in the large-scale growth of graphene on metallic substrates, high densities of wrinkles are commonly observed. Despite their prevalence and potential impact on large-scale graphene electronics, relatively little is known about their structural morphology and electronic properties. Surveying the graphene landscape using atomic force microscopy, we found that wrinkles reach a certain maximum height before folding over. Calculation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
565
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(594 citation statements)
references
References 60 publications
(77 reference statements)
28
565
1
Order By: Relevance
“…Unlike ripples having a modest aspect ratio of ~ 1 and feature sizes of peaks and valleys below 10 nm, wrinkles exhibit a high aspect ratio of 10, and the width ranges from 1 to 10 nm, the height below 15 nm and the length above 100 nm [193]. Wrinkles normally occur on metallic substrates due to the opposite thermal deformation [194,195] and the defect lines [196] on the substrates. Also, the thickness of growth substrate has an effect on the attributes and density of wrinkles.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike ripples having a modest aspect ratio of ~ 1 and feature sizes of peaks and valleys below 10 nm, wrinkles exhibit a high aspect ratio of 10, and the width ranges from 1 to 10 nm, the height below 15 nm and the length above 100 nm [193]. Wrinkles normally occur on metallic substrates due to the opposite thermal deformation [194,195] and the defect lines [196] on the substrates. Also, the thickness of growth substrate has an effect on the attributes and density of wrinkles.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…More specifically, intrinsic ripples are expected to influence the electrical properties of graphene by changing band gap [239], creating polarized carrier puddles [240] and inducing pseudo-magnetic fields [241]. Whereas wrinkles and crumples result in several electronic phenomena, such as electron-hole puddles [189,242], carrier scattering [195,243], band gap opening [244], suppression of weak localization [245] and quantum corrections [246]. …”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…The growth of hexagonal graphene domains on Cu foil by atmospheric pressure CVD was described previously by Vlassiouk et al 11 The graphene islands are shown in SEM image in al. 35 The wrinkle at GB site is much narrower and only plays a secondary role in the increase of the GB resistance in comparison with GB itself. Table 2), at first glance there seems to be a positive correlation between misorientation angle and the GB resistance, and that wrinkles at GB seem to further increase the GB resistance.…”
Section: Grain Boundaries In Cvd Graphenementioning
confidence: 99%
“…4(a) and 4(b). 22 The wrinkles increase the surface area and mass density of graphene. Previously, high densities of wrinkles were observed in large-scale grown graphene on metallic substrates.…”
mentioning
confidence: 99%
“…Previously, high densities of wrinkles were observed in large-scale grown graphene on metallic substrates. 22 These wrinkles are formed due to thermal contraction of the substrate during the cooling process. Besides, nanoscale holes, cracks, and organic/ inorganic residues alter the measured mass density of graphene.…”
mentioning
confidence: 99%